2019
DOI: 10.1002/nop2.240
|View full text |Cite
|
Sign up to set email alerts
|

Turnover intention and job fit among nurses in Ghana: Does psychological climate matter?

Abstract: Aim The study examined the relationship between turnover intention and job fit among Registered Nurses in Ghana. Further analysis was done to explore how nurses' psychological climate has an impact on the relationship between job fit and turnover intention. Design The study adopted the quantitative research approach and the cross‐sectional survey design in collecting data on the variables of interest. Methods Purposive sampling was used to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…It is desirable to work in large hospitals, which often provide better employee benefits, more career development opportunities, and high social status/recognition in the Korean culture. However, large hospitals often cater to patients with more acute medical conditions, requiring intensive and complex nursing care by applying advanced medical equipment or high-skilled nursing procedures (Atitsogbui & Amponsah-Tawiah, 2019). Such patient care responsibilities can be overwhelming, both physically and mentally, to most recently graduated nurses (Shin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is desirable to work in large hospitals, which often provide better employee benefits, more career development opportunities, and high social status/recognition in the Korean culture. However, large hospitals often cater to patients with more acute medical conditions, requiring intensive and complex nursing care by applying advanced medical equipment or high-skilled nursing procedures (Atitsogbui & Amponsah-Tawiah, 2019). Such patient care responsibilities can be overwhelming, both physically and mentally, to most recently graduated nurses (Shin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…R. Edwards (1991) conceptualized intent to leave as a worker’s voluntary decision to exit an organization or job. It is also an indicator of employees not contributing to organizational productivity (Atitsogbui & Amponsah-Tawiah, 2019). Substantial research identified various factors related to intent to leave among nurses, including difficulty in adapting, job satisfaction, person–job fit, individual characteristics (youth, gender: male, marital status: single, and higher educational level), and organizational factors (working overtime, hospital size, and shift rotation), but are still inconclusive about other factors (L.…”
mentioning
confidence: 99%
“…Currently, these are considered dynamic sectors both for the employees and employers; as per recent studies turnover ratio has significantly increased due to hierarchical plateau (Awan & Tahir, 2015). In the broad category, empirical investigations have demonstrated that individuals who have an extraordinary good job fit have higher degrees of job satisfaction, organizational responsibility, and hierarchical recognizable outcomes and expanded work execution, resulted diminished turnover goals and real turnover intentions (Atitsogbui & Amponsah-Tawiah, 2019). Different scholars have exhibited that hierarchical plateau could be utilized as a compelling instrument for procuring and choice of employees.…”
Section: Hierarchical Plateau and Turnover Intentionmentioning
confidence: 99%
“…In addition, a high level of job satisfaction requires much personal engagement. People may feel frustrated and nervous or even leave the job if they sense an imbalance between investment and reward (Atitsogbui and Amponsah-Tawiah, 2019), which indicates an inverted U-shaped relationship between personenvironment fit and job satisfaction. Based on the above findings, the following is proposed: Hypothesis H1a: N-S fit has a decreasing incremental effect on job satisfaction, that is, a positive linear and negative conic effect.…”
Section: Person-environment Fit and Job Satisfactionmentioning
confidence: 99%